Implementation of Blowfish Algorithm for Encryption and Decription on Android-Based QR Code - Zulhamdi Putra; Dedy Abdullah; Erwin Dwika Putra; Yulia Darmi (Jurnal Komputer, Informasi dan Teknologi, 2022)
The development of technology is currently growing very rapidly which allows us to access various kinds of data and information, but there are lots of people who abuse this ability, for example phishing activities that often target data and information owned by individuals and companies. Loss of data and information is very detrimental to individuals and companies, where the data and information can be used as a tool for extortion, used as a fraud tool and even the information can be traded. The main reason for the importance of maintaining the security of information is to protect information from online crimes. One of the techniques designed to protect important and confidential information is a cryptographic technique using the Blowfish algorithm and also a QR Code which functions as second line security. where data and information that has been converted into a QR Code cannot be changed. The purpose of this study is to apply the Blowfish Algorithm for Encryption and Decryption of the QR Code into an android-based application system. The results of this study are: The blowfish algorithm can be implemented into an android-based application. Plaintext which is converted into ciphertext using the blowfish algorithm can be used as a QR Code using a QR Code generator. A QR code is up to 7089 numeric digits and 4296 alphanumeric characters. The amount of information will affect the QR Code module, so the symbols in the QR Code will become more complicated. This application has received an assessment from respondents from users with an average value (6.5) with the category of choice "agree".